2012
DOI: 10.1016/j.rehab.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

What is the best support surface in prevention and treatment, as of 2012, for a patient at risk and/or suffering from pressure ulcer sore? Developing French guidelines for clinical practice

Abstract: Support surfaces are recommended in prevention and treatment of patients at risk and/or already suffering from pressure ulcer, and their use should constitute part of an overall preventive or curative strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…18,24 Especialistas têm alertado para a importância do conhecimento baseado em evidências dos profissionais de saúde e gestores responsáveis pela escolha e aquisição de produtos para a prevenção da UP, visto que muitos destes não atendem as diretrizes de prevenção, e seu uso pode aumentar o risco de desenvolvimento da UP. 21,25 A mudança de decúbito, considerada um componente essencial na prevenção da UP por aliviar a carga em áreas de alta pressão, vem sendo discutida em relação a sua eficácia e quais protocolos de reposicionamento são mais eficazes. 19 Pesquisadores desenvolveram um dispositivo de leito para mapeamento contínuo da pressão (DLMCP), que consiste em um tapete com células sensoras de pressão, com um display que exibe imagens de pressão do corpo em tempo real.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…18,24 Especialistas têm alertado para a importância do conhecimento baseado em evidências dos profissionais de saúde e gestores responsáveis pela escolha e aquisição de produtos para a prevenção da UP, visto que muitos destes não atendem as diretrizes de prevenção, e seu uso pode aumentar o risco de desenvolvimento da UP. 21,25 A mudança de decúbito, considerada um componente essencial na prevenção da UP por aliviar a carga em áreas de alta pressão, vem sendo discutida em relação a sua eficácia e quais protocolos de reposicionamento são mais eficazes. 19 Pesquisadores desenvolveram um dispositivo de leito para mapeamento contínuo da pressão (DLMCP), que consiste em um tapete com células sensoras de pressão, com um display que exibe imagens de pressão do corpo em tempo real.…”
Section: Resultsunclassified
“…Os autores recomendam o uso de superfícies de apoio na prevenção e tratamento da UP e salientam que seu uso deve constituir parte de uma estratégia preventiva e curativa em geral. 25 O filme transparente de poliuretano (FTP) tem sido indicado para a prevenção de UP em pele intacta, apesar da escassez de estudos científicos para provar sua efetividade. 28 Especialistas avaliaram a efetividade do FTP na prevenção de UP no calcâneo.…”
Section: Conclusãounclassified
“…They report that APAMs are likely to be more effective than standard hospital mattress; the comparison of the effectiveness of different APAMs, on the other hand, showed no tendency in favour of one or the other. 4,16 A randomised study (n=447 patients), 17 mentioned in 2012 in the French guidelines, 18 compared the efficacy of an APAM without a turning protocol with that of a VFM with a turning protocol every four hours. This study reported a similar incidence of category II-IV PUs in the two groups (15.3% APAM and 15.6% VFM), with more severe PUs in the APAM group.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the use of support surfaces 20. Pressure ulcer prevention and control should be based on a comprehensive, holistic assessment and treatment, and it is important to note that the support surface is only a tool for pressure ulcer prevention and reduction, and its use must be within the framework of a holistic patient management strategy that emphasises stress targeting and nutritional care 15,16 Level 5b…”
Section: Level 5cmentioning
confidence: 99%